MOBILE MECHANICAL DEVICE FOR VINEYARD CARE AND PRELIMINARY SYNTHESIS OF ITS MAIN PARAMETERS - Iminov Bahramali Ikromzhanovich (Bright Mind Publishing, 2025)
In order to facilitate the process of caring for vineyards, to save the physical strength of gardeners, the authors offer gardeners a new "Mobile mechanical ladder" - a mobile device.
Keywords: vineyard, pantograph, lifting mechanism, cab, steering wheel, synthesis.